Increased nuchal translucency in children with congenital heart defects and normal karyotype—is there a correlation with mortality? - Kristensen, Rasmus; Omann, Camilla; Gaynor, J. William; Rode, Line; Ekelund, Charlotte K.; Hjortdal, Vibeke E. (Frontiers in Pediatrics, 2023)
Objectives Our objective was to investigate if an increased nuchal translucency (NT) was associated with higher mortality in chromosomally normal children with congenital heart defects (CHD) Methods In a nationwide cohort using population-based registers, we identified 5,633 liveborn children in Denmark with a pre- or postnatal diagnosis of CHD from 2008-2018 (incidence of CHD 0.7%). Children with chromosomal abnormalities and non-singletons were excluded. The final cohort compromised 4,469 children. An increased NT was defined as NT>95th-centile. Children with a NT>95th-centile vs. NT<95th-centile including subgroups of simple- and complex CHD were compared. Mortality was defined as death from natural causes, and mortalities were compared among groups. Survival analysis with Cox-regression was used to compare rates of mortality. Analyses were adjusted for mediators (possibly explanatory factors between increased NT and higher mortality): preeclampsia, preterm birth and small for gestational age. And for confounding effects of extracardiac anomalies and cardiac intervention, due to their close association to both the exposure and the outcome (i.e. confounders). Results Of the 4,469 children with CHD, 754 (17%) had complex CHD and 3,715 (83%) simple CHD. In the combined group of CHDs the mortality rate was not increased when comparing those with a NT>95th-centile to those with a NT<95th-centile (Hazard ratio (HR) 1.6, 95%CI 0.8;3.4, p=0.2). In simple CHD there was a significantly higher mortality rate with a HR of 3.2 (95%CI: 1.1;9.2, p=0.03) when having a NT >95th centile. Complex CHD had no differences in mortality rate between a NT>95th-centile and NT<95th-centile (HR 1.1, 95%CI: 0.4;3.2, p=0.8). All analysis adjusted for severity of CHD, cardiac operation and extracardiac anomalies. Due to limited numbers the association to mortality for a NT>99th centile (>3.5 mm) could not be assessed. Adjustment for mediating (preeclampsia, preterm birth, small for gestational age) and confounding variables (extracardiac anomalies, cardiac intervention) did not alter the associations significantly, except for extracardiac anomalies in simple CHD. Conclusion An increased NT>95th-centile is correlated with higher mortality in children with simple CHD, but the underlying cause is unknown and undetected abnormal genetics might explain the correlation rather than the increased NT itself, hence further research is warranted.